Activism in LGBTIQ+ film festivals. Queer approach in Juanma Carrillo´s work - Josué Bernabé Hernández (Comunicación y Género, 2018)
LGTBIQ + film festivals born from social movements work as a form of activism, offering a view from within the community itself and offering, through the short film, some of the most transgressive and critical stories with the representation system of the different identities. Starting from the Queer Theory, the tools are taken to approach this object of study, through the filmic analysis of the work of Juanma Carrillo, where it will be explicit as the images have the transforming power in the perception of different subjectivities, articulating a alternative discourse to the hegemonic heterosexist look.